Ventilatory thresholds assessment from heart rate variability during an incremental exhaustive running test - Cottin, F.; Medigue, C.; Lopes, P.; Lepretre, P.-M.; Heubert, R.; Billat, V. (International Journal of Sports Medicine, 2007)
The present study examined whether the ventilatory thresholds during an incremental exhaustive running test could be determined using heart rate variability (HRV) analysis. Beat-to-beat RR interval, V·O2, V·CO2 and V·E of twelve professional soccer players were collected during an incremental test performed on a track until exhaustion. The "smoothed pseudo Wigner-Ville distribution" (SPWVD) time-frequency analysis method was applied to the RR time series to compute the usual HRV components vs. running speed stages. The ventilatory equivalent method was used to assess the ventilatory thresholds (VT1 and VT2) from respiratory components. In addition, ventilatory thresholds were assessed from the instantaneous components of respiratory sinus arrhythmia (RSA) by two different methods: 1) from the high frequency peak of HRV (fHF), and 2) from the product of the spectral power contained within the high frequency band (0.15 Hz to fmax) by fHF (HF · fHF) giving two thresholds: HFT1 and HFT2. Since the relationship between fHF and running speed was linear for all subjects, the VTs could not be determined from fHF. No significant differences were found between respective running speeds at VT1 vs. HFT1 (9.83 ± 1.12 vs. 10.08 ± 1.29 km · h-1, n.s.) nor between the respective running speeds at VT2 vs. HFT2 (12.55 ± 1.31 vs. 12.58 ± 1.33 km · h-1, n.s.). Linear regression analysis showed a strong correlation between VT1 vs. HFT1 (R2 = 0.94, p < 0.001) and VT2 vs. HFT2 (R2 = 0.96, p < 0.001). The Bland-Altman plot analysis reveals that the assessment from RSA gives an accurate estimation of the VTs, with HF · fHF providing a reliable index for the ventilatory thresholds detection. This study has shown that VTs could be assessed during an incremental running test performed on a track using a simple beat-to-beat heart rate monitor, which is less expensive and complex than the classical respiratory measurement devices.